A Reassessment of Phylogenetic Relationships in Class Oligohymenophorea (Protista, Ciliophora) Based on Updated Multigene Data - Bailin Li; Yumeng Song; Xiang Wang; Qiyue Zhao; Menghan Liu; Lihui Liu; Xuming Pan; Zhenzhen Yi (Ecology and Evolution, 2025)
ABSTRACT Within the ciliate class Oligohymenophorea, many evolutionary relationships among taxa remain unresolved. This study incorporates 97 new sequences from 30 oligohymenophorean populations, including nuclear small subunit ribosomal (SSU‐rRNA) genes, nuclear ITS1‐5.8S‐ITS2 rRNA regions, nuclear large subunit ribosomal (LSU‐rRNA) genes, mitochondrial cytochrome oxidase c subunit I (cox 1) genes, and mitochondrial small subunit ribosomal RNA (mtSSU‐rRNA) genes. With the addition of these new sequences, we performed comprehensive multigene phylogenetic analyses of Oligohymenophorea. The main findings are: (1) Utilizing multiple genes is instrumental in improving phylogenetic relationships within class Oligohymenophorea; (2) class Oligohymenophorea is divided into two distinct groups: (i) encompassing the subclass Hymenostomatia, Scuticociliatia, Apostomatia, Astomatia, and Urocentria; and (ii) comprising the subclasses Peniculia and Peritrichia; (3) Revising the phylogenetic placement of the subclass Urocentrida reveals its transitional role as a taxon between Group I and Group II. It emerges as a sister clade to Hymenostomatia; (4) the phylogenetic positions of Astomatia and Apostomatia within the clade ‘SAA’ become clearer; and (5) the order Loxocephalida represents an early member of Scuticociliatia and serves as a potential prototype for this taxonomic group. This study provides more information for understanding the evolutionary relationships within Oligohymenophorea.